Peran Ayah dalam Pembentukan Karakter Anak: Telaah Surah Luqman Ayat 12-14 - Ma’arif Tarigan, Mhd. Rafi’i; Mahabatul Ainiah, Eka; Lubis, Aswan; Yunus Lubis, Muhammad; Mustika Amalia, Dian (Generasi Emas, 2023)
Fathers have a characteristic role in the family, namely the breadwinner, in this case the father is responsible for all family needs. One of the roles of fathers in educating children is modeling to children in terms of wisdom and being responsible for planning and decision making in a matter. This study aims to understand the figure of the father's role in teaching character education to children in Surah Luqman verses 12-14. This exploration uses a literature study research method with a descriptive-analytical approach. The results of this study indicate that in Surah Luqman verses 12-14 show that Luqman advised his son with advice that was not patronizing and there were also no accusations, because parents only want children to be good and only parents are their children's advisors. The character of a good father in Islam is depicted in Luqman, who always takes care of the child with love, advises the child with gentle words, and instills religious character education to the child.